Vibrational analysis of neat liquid tert-butylmethylether - Beć, K.B.; Kwiatek, A.; Hawranek, J.P. (Journal of molecular liquids, 2014)
Among aliphatic ethers, the most known is tert-butylmethylether (TBME), mainly for its significance in the fuel industry. It was the subject of numerous investigations, including industrial, environmental and medical studies. The literature however is lacking of any insightful infrared studies of TBME in neat liquid phase. In this work we determined the optical constants of TBME, from transmission studies in the IR range (11,700–560cm−1). The use of quantitative thin film recording techniques was essential due to the high absorption of neat liquids in the MIR range. Low temperature matrix investigation was also carried out, to elucidate details of the vibrational spectrum of TBME. The experiment was supported by an anharmonic vibrational analysis including the simulation of experimental spectrum, based on the B2PLYP/N07D level of theory. The chosen method delivered good results with a relatively modest computational cost. •The complex refractive index of liquid tert-butylmethylether was determined.•Low temperature matrix isolation recordings were also carried out.•The anharmonic vibrational analysis (B2PLYP/N07D) was performed.•Band identification in neat liquid TBME and matrix spectra was carried out.